Hypertrophic and polypose changes in the synonasal mucosa in children with atopic bronchial asthma and allergic rhinitis - N. I. Eruslankin; A. A. Vagina; S. V. Krasilnikova; A. A. Khramov; V. A. Bulgakov; I. I. Balabolkin; T. I. Eliseeva (Аллергология и Иммунология в Педиатрии)
Introduction. Hypertrophic and polyposis changes in the synonasal mucosa (SNM) in patients with bronchial asthma (BA) and allergic rhinitis (AR) negatively affect the course of these diseases. The debut of their formation can be observed already in childhood, but there is currently no precise information about the course of this pathology in children with BA and AR. The features of systemic immune regulation in these patients are also not studied. Purpose of the study. To study the effect of hypertrophic and polyposis changes in SNM on the clinical characteristics of AR in children with BA and on their relationship with the content of serum immunoglobulins A, M, G and E. Materials and methods. We examined 137 patients with atopic BA and AR at the age of 10.0 [7.0; 13.0] years, of which boys — 75.2% (103/137). Patients underwent routine examination of ENT organs and video endorhinolaryngoscopy, if indicated — CT scan of the paranasal sinuses. Determination of the content of total IgE, as well as IgA, IgM, IgG in blood serum was carried out by the enzyme-linked immunosorbent assay "VectorBest" (Russia). Results. In 19.7% (27/137) children, changes in SNM were revealed in the form of local hypertrophy of the medial surface of the turbinates, in 10.9% (15/137) polyposis changes in SNM. These changes in SNM were statistically significantly more frequent in patients with moderate and severe AR (χ2=57.7; p<0.001). The content of serum total IgE was comparable in children with the absence and presence of synonasal hypertrophy (p=0.65), as well as in serum IgM (p=0.74). At the same time, the serum IgA content in children with synonasal hypertrophy unexpectedly turned out to be statistically significantly higher (p=0.024), and the serum IgG content had a clear tendency to increase (p=0.053) compared with children who did not have hypertrophic changes in SNM. Conclusion. The course of AR in children with BA may be accompanied by the formation of hypertrophic and polyposis changes in the SNM, which are associated with a more severe course of AR and with an increased expression of synonasal symptoms. Children with hypertrophic changes in SNM were found to have a statistically significantly higher level of total serum IgA compared with children without SNM hypertrophy. Apparently, patients with BA and AR with hypertrophic changes in SNM have a unique systemic immunological profile that requires serious study.